(untitled) (Global Journal of Management and Business Research, 2023)
For an educational system or any system for that matter the terms which lift the weight are management and leadership By the dawn of the past century much attention has been given to these two terms for their magnitude of importance and implication When it comes to the educational facility and the question of allocating the available resources to achieve the maximum goals it becomes crystal clear that a figure with influence is needed in the educational playground so to speak This review shed some light on these points and illustrates their use